Th17 cells in primary Sjögren's syndrome: Pathogenicity and plasticity. (February 2018) - Verstappen, Gwenny M.; Corneth, Odilia B.J.; Bootsma, Hendrika; Kroese, Frans G.M.
Abstract: Th17 cells play an important physiological role at mucosal barriers, and are involved in inflammatory responses to pathogens. Th17 cells and their signature cytokine IL-17 are also present in salivary gland lesions of primary Sjögren's syndrome (pSS) patients and can be elevated in their peripheral blood. In pSS patients, clear correlations between increased Th17 cell activity and symptoms of the disease have not been found, but Th17 cells may contribute to disease progression, for example by supporting autoreactive B cell responses. In mouse models of pSS, Th17 cells play an important role in pathogenesis, particularly at disease onset, when there is a disturbed balance between T effector and T regulatory cells. Studying the pathogenicity of Th17 cells in humans is complicated due to the plasticity of this cell subset, allowing them to obtain different effector functions depending on the local environment. Th17 cells can develop towards Th17.1 cells, producing both IL-17 and IFN-γ, or even towards Th1-like cells producing IFN-γ in the absence of IL-17. These effector subsets may be more pathogenic than bona fide Th17 cells. Co-expression of IFN-γ by Th17 cells has been shown to promote chronic inflammation in several autoimmune diseases and may also contribute to pSS pathogenesis. In line with the noticeable role of IL-17 in pSS mouse models, interference with Th17 cell generation, recruitment or effector functions (e.g. IL-17 inhibition) can prevent or ameliorate disease in these models. Therapies targeting Th17 cells or IL-17 have not been tested so far in pSS patients, although treatment with rituximab seems to lower local and systemic IL-17 protein levels, and to a lesser extent also chemokine receptor-defined Th17 cells. In this review we discuss current knowledge of pathogenicity and plasticity of Th17 cells in human pSS and murine models of pSS. We postulate that plasticity towards Th17.1 cells in pSS may enhance pathogenicity of Th17 cells at the main target sites of the disease, i.e. salivary and lacrimal glands. Highlights: Th17 cells and IL-17 are present in glandular tissue of pSS patients. Nevertheless, the contribution of Th17 cells to pSS pathogenesis remains inconclusive. In mouse models of SS, Th17 cells are important drivers of disease. Plasticity of Th17 cells may underlie ambiguity about the role of Th17 cells in pSS pathogenesis.